El mito del agua en la literatura mexicana y 2666 de Roberto Bolaño - Ursula Hennigfeld (Prof. Dr. Vittoria Borsò, Prof. Dr. Frank Leinen, Jun.-Prof. Dr. Yasmin Temelli, Prof. Dr. Guido Rings, 2014)
The article presents an analysis of the aquatic metaphors in Roberto Bolaño’s novel 2666, relating them to cultural myths about water. First, some theoretical considerations about the myth of water are presented (L’eau et les rêves by Gaston Bachelard, ‘L’eau et la folie’ by Michel Foucault and Communitas by Roberto Esposito), then some Mexican literary discourses that deal with water (poems by Amado Nervo and José Gorostiza, the novel Los muros de agua by José Revueltas) to end in an analysis of Bolaño’s novel. Examples of dreams with water are interpreted (Morini’s dream of the swimming pool, Hans Reiter’s escape through the river), of mysterious events (Pelletier who discovers a lump on the beach, Hans Reiter as the "seaweed boy"), of dire omens (the murder of Marius Newell) or of paradoxical analogies (Lalo Cura who compares the sea with the desert).